Distinguishing predisposing factors for enamel hypoplasia and molar-incisor hypomineralization in children in Ile-Ife, Nigeria - Oluwaseyi Dada Temilola; Morenike Oluwatoyin Folayan (Universidade Estadual de Campinas, 2016)
Aim: To determine if the prevalence of enamel hypoplasia, molar-incisor hypomineralisation (MIH) and deciduous molar hypomineralisation (DMH) is associated with the socioeconomic status of the child and to determine the prevalence of enamel hypoplasia and MIH/DMH comorbidity in the study population. Methods: Information was collected on the sex and socioeconomic status of the 1,169 study participants' resident in Ile-Ife, Nigeria, recruited through a household survey. The children were clinically examined to assess for the presence of enamel hypoplasia, MIH and DMH. Associations between sex, socioeconomic status and the prevalence of enamel hypoplasia, MIH and DMH were determined. The proportion of children with enamel hypoplasia and MIH/DMH co-morbidity was also determined. Results: Among the 1,169 study participants, 47(4.0%) had MIH, 15 (1.3%) had DMH and 161 (13.8%) had enamel hypoplasia. One (0.09%) study participant had MIH/DMH co-morbidity, 12 (1.0%) had DMH/enamel hypoplasia co-morbidity, and 9 (0.8%) had MIH/hypoplasia co-morbidity. There was no significant association between the socioeconomic status and presence of enamel hypoplasia (p=0.22), MIH (p=0.78) or DMH (p=1.00). Conclusions: The socioeconomic status cannot be used as a distinguishing factor for enamel hypoplasia, MIH and DMH. The possibility of co-existence of enamel hypoplasia and MIH/DMH makes it imperative to find ways to distinguish between the lesions.